The Direct and Indirect Costs of Treating the Victims of the 2016 Nice Terror Attacks in a Single Pediatric Hospital. (7th June 2022) - Solla, Federico; Ellenberg, Eytan; Rampal, Virginie; Margaine, Julien; Musoff, Charles; Taragin, Mark; Tran, Antoine; Ostfeld, Ishay
Abstract: Objective: To analyze the cost of the terror attack in Nice in a single pediatric institution. Methods: We carried out descriptive analyses of the data coming from the Lenval University Children's Hospital of Nice database after the July 14, 2016 terror attack. The medical cost for each patient was estimated from the invoice that the hospital sent to public insurance. The indirect costs were calculated from the hospital's accounting, as the items that were previously absent or the difference between costs in 2016 versus the previous year. Results: The costs total 1.56 million USD, corresponding to 2% of Lenval Hospital's 2016 annual budget. Direct medical costs represented 9% of the total cost. The indirect costs were related to human resources (overtime, sick leave), revenue shortfall, and security and psychiatric reinforcement. Conclusion: Indirect costs had a greater impact than did direct medical costs. Examining the level and variety of direct and indirect costs will lead to a better understanding of the consequences of terror acts and to improved preparation for future attacks.